HPLC-ICP-MS speciation analysis of arsenic in river water of Sungai Kinta Malaysia - Norshidah, B.; Norashikin, S.; Rozita, O.; Md, Z.S.; Hafizan, J.; Saari, S.R. (2010)
The toxicity and carcinogenicity of arsenic depend on its species. A procedure for the separation of the arsenic species namely arsenite As (III) and arsenate As (V) by liquid chromatography coupled to inductively coupled plasma mass spectrometry (LC-ICP-MS) is described. It has been successfully applied to the analysis of arsenic in river water of Sungai Kinta, Malaysia. No interference of (40) Ar, Cl-35 and As-75 was observed using the developed method. The separation of arsenic species produced peaks of As (III) at 1.6 min and As (V) at 4.8 mm. The detection limits were found to be 1.0 and 0.5 ppb for As (III) and As (V) respectively. Standard addition method confirmed the accuracy with. acceptable recoveries of As (III) and As (V). The results revealed that As (V) was more prominent than As (III) in most sampling sites.